The Equivalent of the Translation Parables in the Bible - Maximus Taeki Sila Koa (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
In doing the translation, the translator should be able to retain the meaning in the target language to make an equivalent translation. According to Catford (1974: 50) translation equivalence occurs when a SL text and TL text of items are relatable to the same features of substance. He also states that the aim in total translation must, therefore, be to select TL equivalents not with the same meaning as the SL items, but with the greatest possible overlap of situational range. From that statement, it can be concluded that the translation is the process to transfer the same function by using the natural forms from SL into the TL. Generally, this article is focused on the analysis of the types of parables and their translation equivalents in the target language on the Bible. The figure of speech is the style of language used by the writer to convey the message imaginatively or as a glossary language used to create a certain effect and make alive literary works. Parables are part of the figure of speech. Parables are short stories taken from a natural state of life or a general state of life and illustrate moral or religious lessons. Nelson (1995) in Booth (2005) states that a parable is a short simple story designed to communicate spiritual truth, religious principle or moral lesson. The data of this research were obtained from the New Testament Holy Bible. The main theory applied is the theory from (Larson 1998) entitled Meaning Based Translation. And some books that are relevant to the topic of this paper. The result of this research shows that in the Gospels, the writer found two categories figure of speech that use by Jesus Christ in His preaching, they are the parables that use metaphor and the parables that use simile. The context of the parables is to describe the word of God and the truth of life that is the Kingdom of Heaven.